Strategi Bauran Promosi (Promotion Mix) dalam Meningkatkan Penjualan pada KC Photography Tombolo Pao, Kabupaten Gowa - Prasetya, Arya; Idris, M. Abduh; Merdekawaty, Etha Gustin; Arief, Syarifuddin; Sudirman, Sudirman (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to explore how KC Photography's promotional strategies effectively attract consumer interest. The research is qualitative in nature and is grounded in the Promotion Mix Theory, focusing on Advertising and Sales Promotion. Data collection was conducted through observation, in-depth interviews, and documentation. Data analysis involved processes such as data reduction, data presentation, conclusion drawing, and validation through triangulation techniques. The study's informants were selected using purposive sampling. The findings indicate that KC Photography's implementation of the Promotion Mix strategy has successfully drawn consumer interest in the services offered, as evidenced by the feedback from the informants regarding the promotional activities undertaken by KC Photography.